"Gay Now": Bisexual Erasure in Supernatural Media from 1983 to 2003. Issue 1 (2nd January 2020) - de Barros, Ana Carolina
Abstract: Bisexual representation in media has historically lagged behind gay and lesbian representation. Given that bisexual people experience poorer mental health measures when compared to heterosexual and gay people, positive representation could have a significant impact on bettering bisexual people's lives. Additionally, examining historical trends of bisexual representation may help us better contextualize the current state of bisexual representation. This paper conducts a thematic analysis of three bisexual women from two texts: Miriam and Sarah from The Hunger, a 1983 movie, and Willow from Buffy the Vampire Slayer, a 1997–2003 television show. Although Miriam, Sarah, and Willow all exhibit attraction toward both men and women, they are commonly referred to as lesbians. The erasure of potential readings of their sexualities as bisexual occurs through three streams: downplaying attraction to men, describing erotic scenes as "lesbian, " and formulating bisexuality as an invisible identity. Further, the supernatural context of these texts creates a connection between bisexuality and monstrosity. However, these texts occasionally subvert traditional methods of erasure and are thus praised as progressive, rather than criticized, by reviewers. These texts imply that potential bisexual readings of characters in the 1980s and 1990s were erased by both the texts themselves and their reviewers, in favor of characterizing progression of lesbian representation.